Perbandingan Arah Kebijakan Luar Negeri Pasca Perubahan Sistem Politik Indonesia 1998 dan Myanmar 2011 - Albert Saputra (Jurnal Ilmu Hubungan Internasional LINO, 2025)
This research compares Indonesia's foreign policy orientation post-1998 Reformasi with Myanmar's post-2011 political transition. Through a qualitative approach with a comparative study design, this research examines how the change in political system from an authoritarian regime to a democratic system affected the foreign policy orientation of both countries. The main findings show that Indonesia successfully reconstructed its international image as the world's third largest democracy through multilateral diplomacy, active participation in ASEAN, and promotion of human rights. In contrast, Myanmar, despite showing significant political and economic reforms under President Thein Sein, still faces structural obstacles due to the military's dominance in the political system. The research also highlights how internal dynamics - such as political elite pressure and public opinion - as well as external contexts such as pressure from the international community and position in the international system, shape post-transition foreign policy. The case of Indonesia shows a deeper and more sustained transformation than Myanmar, where reforms were limited and controlled. These results reinforce the theory that democratization does not automatically result in a more progressive foreign policy, but rather is influenced by a complex interaction between domestic and international variables. Further recommendations are directed towards the study of the role of non-state actors and social media in influencing the foreign policy orientation of transition countries.